Ecological specialization in mycorrhizal symbiosis leads to rarity in an endangered orchid - Swarts, N.; Sinclair, E.; Francis, A.; Dixon, Kingsley (Wiley-Blackwell Publishing, 2010)
Terrestrial orchid germination, growth and development are closely linked to the establishment and maintenance of a relationship with a mycorrhizal fungus. Mycorrhizal dependency and specificity varies considerably between orchid taxa but the degree to which this underpins rarity in orchids is unknown. In the context of examining orchid rarity, large scale in vitro and in situ germination trials complemented by DNA sequencing were used to investigate ecological specialization in the mycorrhizal interaction of the rare terrestrial orchid Caladenia huegelii. Common and widespread sympatric orchid congeners were used for comparative purposes. Germination trials revealed an absolute requirement for mycorrhisation with compatibility barriers to germination limiting C. huegelii to a highly specific and range limited, efficacious mycorrhizal fungus. DNA sequencing confirmed fidelity between orchid and fungus across the distribution range of C. huegelii and at key life history stages within its life cycle. It was also revealed that common congeners could swap or share fungal partners including the fungus associated with the rare orchid but not vice versa. Data from this study provides evidence for orchid rarity as a cause and consequence of high mycorrhizal specialization. This interaction must be taken into account in efforts to mitigate the significant extinction risk for this species from anthropogenically induced habitat change and illustrates the importance of understanding fungal specificity in orchid ecology and conservation. © 2010 Blackwell Publishing Ltd.